Development of Learning Model Tools STEAM-based SCT in Wetland Environment Theme - Rusmansyah Rusmansyah; Norsalehah Norsalehah; Leny Leny; R A Sholeha (Journal of Educational Chemistry (JEC), 2022)
This study aimed to produce learning tools that meet the eligibility criteria based on the level of validity, practicality, and effectiveness. This study used methods of RD with a 4D development model. The study was conducted with 5 students on individual trials, 9 students on small group trials, and 35 students on limited trials. The results showed: (1) Validity, expert validation results for lesson plans, and students' worksheets were obtained at 99.3% and 87.3% (accurate); (2) Practicality, from the results of students' responses to questionnaires on individual trials of 3.44 (good), small group trials of 4.29 (good), student response questionnaires of 3.93 (good), teacher's response questionnaires on learning and lesson plans of 4.70 and 4.30 (very good) and observations of the implementation of learning using lesson plans of 4.29 (excellent); (3) The effectiveness was seen in the average N-gain score for creative thinking abilities and self-efficacy of students, namely 0.54 (medium) and 0.73 (high). Overall the development of this learning device had met the eligibility criteria to train students' creative thinking skills and self-efficacy.